Impact of design changes in construction project / Nurul Huda Muhamad and Mohammad Fadhil Mohammad - Nurul Huda, Muhamad; Mohammad Fadhil, Mohammad (Universiti Teknologi MARA, Perak, 2018)
Design changes in construction projects are always going to happen and cannot be avoided. Design changes are the primary contributor to disruption of time and cost performance of construction projects. Previous research in this domain lacks of detail studies on systematic review on the existing literature. This paper reviewed literature published in peer-reviewed journals and conference proceedings in the construction management field and had emailed several questions to the expert in construction industry. The objectives were to recognize the causes and impacts of design changes on project performance and to provide insights for future studies in Malaysian context. The findings indicate that design changes originate mainly from the owner side are identified as important causing factors to time overruns and cost overruns. This paper proposes framework for the management of design changes in construction projects.